PERSEPSI MASYARAKAT TERHADAP PENGGUNAAN LAHAN SAWAH DI DESA TOUNELET SATU KECAMATAN SONDER - Lovi Cherry Valentine Katuuk; Vicky R. B. Moniaga; Juliana R. Mandei (Sam Ratulangi University, 2018)
This study aims to determine the Perceptions of the Community Against Rice Land Use In Tounelet Village One, Sub-district Sonder. This research was conducted from November 2017 until January 2018, starting from preparation until preparation of research report. The research site is Tounelet Village One, Sub-district Sonder. This research uses primary data and secondary data. Primary data was obtained from 30 respondents by using questionnaire, while secondary data was obtained from print media and online media and from journals in the literature related to this research. Sampling method in this research using purposive sampling method. Result of research indicate that public perception toward Wetland Field Estate is good with perception index 77.27%. The community agrees with the use of existing paddy fields in Tounelet One village, Pigs help both as rice fields and as pig farms.